2015
DOI: 10.1590/s0102-865020150100000001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Sphingosine-1-phosphate (S1P) on the cerebral vasospasm after subarachnoid hemorrhage in rabbits

Abstract: PURPOSE: To demonstrate the relationship between of sphingosine-1-phosphate (S1P) expression and subarachnoid hemorrhage (SAH). METHODS:The basilar arteries from a "double-hemorrhage" rabbit model of SAH were used to investigate the relation between S1P expression and SAH. Various symptoms, including blood clots, basilar artery cross-sectional area, and S1P phosphatase expression were measured at day 3, 5, 7, 9. RESULTS:The expression of S1P was enhanced in the cerebral vasospasm after subarachnoid hemorrhage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…(178) Interestingly, S1P 3 receptors are also reported to mediate the potent constriction of cerebral arteries by S1P,(40) thus providing a novel target of S1P 1 /S1P 3 system in regulating the vascular response after SAH. Tang et al also observed the expression of S1P on the cerebral vasospasm after SAH using a “double hemorrhage” model in rabbit,(179) and they found S1P expression a new marker for the development of cerebral vasospasm. Also, targeting either TNF-α or the S1P signaling pathway after SAH attenuated neuronal apoptosis and improved neurological outcome.…”
Section: Stroke and The Sphingolipid Pathwaymentioning
confidence: 97%
See 1 more Smart Citation
“…(178) Interestingly, S1P 3 receptors are also reported to mediate the potent constriction of cerebral arteries by S1P,(40) thus providing a novel target of S1P 1 /S1P 3 system in regulating the vascular response after SAH. Tang et al also observed the expression of S1P on the cerebral vasospasm after SAH using a “double hemorrhage” model in rabbit,(179) and they found S1P expression a new marker for the development of cerebral vasospasm. Also, targeting either TNF-α or the S1P signaling pathway after SAH attenuated neuronal apoptosis and improved neurological outcome.…”
Section: Stroke and The Sphingolipid Pathwaymentioning
confidence: 97%
“…(32, 37, 38, 175179) S1P was first found to induce vasoconstriction in canine basilar artery and SPC was determined to be a novel mediator of Rho-kinase induced cerebral vasospasm and act as a proinflammatory mediator in cerebral arteries. Further, SPC cerebrospinal fluid (CSF) levels are elevated in SAH patients.…”
Section: Stroke and The Sphingolipid Pathwaymentioning
confidence: 99%
“…S1P has been shown in vitro to induce vasoconstriction in mouse middle cerebral arteries [ 14 ] and both in vitro and in vivo in canine basilar arteries [ 42 ]. S1P expression has also been demonstrated to be elevated in vasospastic vessels from a rat model of SAH [ 43 ]. In keeping with this, vascular tone was reduced in SphK2 knock-out mouse cerebral vessels with decreased S1P signalling [ 14 ].…”
Section: S1p Signalling After Asahmentioning
confidence: 99%